Analisis Pengaruh Sektor Pertanian dan Industri Pengolahan Terhadap Tingkat Kemiskinan di Kabupaten Kerinci - Tan, Rafnir; Delfia, Elka (Jurnal Ekonomi Sakti, 2018)
The purpose of this research is to know the Influence of Agricultural Sector and Processing Industry sector to Poverty in Kerinci Regency 2010-2014. Operational Variables in this study is the element of research that gives guidance as measured variables, while the variables referred to in this study are: Poverty Level (Variable Y), is a condition that is measured by comparing the number of population with the number of poor people in a certain year expressed in percent (%), Agricultural Sector (Variable X1), is the value of agricultural production which is donated to GRDP on the basis of current prices from 2010-2014 stated in rupiah, Manufacturing Processing Sector (Variable X2), is the value of industrial production processing in Kerinci Regency which is donated to GRDP over current prices from 2010-2014 stated in rupiah.